Nature of Communication In The Perspective of Surah Al-Hujarat Verse 11-13 - Dewi Mukarromah; Anita Puji Astutik (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article looks at the morals of communication through the lens of Surah Al-Hujarat Verse 11-13. Sheikh Wahbah Zuhaili's study of Munir's Tafsir. This study aims to educate the public about the value of honest communication. Honest communication is the foundation of life and religion for everyone. Morals instruct us to constantly have excellent character and behavior in our interactions with God and others. The method is qualitative, and it entails data mining or library article. The term